Thermogravimetric analysis of OMMT filled HDPE/EPDM treated EB irradiation - Jamal, Nur Ayuni; Anuar, Hazleen; Hassan, Noor Azlina; Abd Razak, Shamsul Bahri (Trans Tech Publications, Switzerland, 2012)
In the current study, high density polyethylene (HDPE)/ ethylene propylene diene monomer (EPDM) blend and organophilic montmorillonite (OMMT) filled HDPE/EPDM was develop aiming at enhancing the thermal properties. Maleic anhydride polyethylene (MAPE) agent and electron beam (EB) irradiation technique were applied as HDPE/EPDM blend and OMMT filled HDPE/EPDM treatments. HDPE/EPDM blend and OMMT filled HDPE/EPDM were first prepared via melt intercalation technique at 4 vol% OMMT loading. For EB irradiation technique, the absorbed dose was set at 100 kGy. The effectiveness of these surface modification treatments were compared with control one (no surface modification) and analyzed based on the thermal test as well as transmission electron microscope (TEM). It was found that the thermal properties of both HDPE/EPDM blend and OMMT filled HDPE/EPDM were significantly enhanced by EB irradiation technique as compared to the control and MAPE systems. Transmission electron microscope (TEM) illustrated the mixed intercalated and partial exfoliated structures of OMMT filled HDPE/EPDM with EB irradiation technique.